Development and validation of a mid-water baited stereo-video technique for investigating pelagic fish assemblages - Santana-Garcon, J.; Newman, S.; Harvey, Euan (Elsevier, 2014)
Understanding the abundance, demographics and composition of pelagic fish communities has historically relied on fisheries catch data or destructive fishery-independent methods. Here, we test and validate the use of a pelagic stereo-Baited Remote Underwater Video system (BRUVs) as a non-destructive, fishery-independent approach to study pelagic fish assemblages. We investigated whether differences in the vertical composition of fish assemblages could be detected with pelagic stereo-BRUVs by sampling at different depths in the water column. The effects of soak time and replication on the precision and cost of sampling were explored to allow for the optimization and standardization of future pelagic stereo-BRUVs studies. Pelagic stereo-BRUVs effectively identified 43 fish taxa from 18 different families in the mid-water, 5 and 20 m below the surface, in the Ningaloo Marine Park (Western Australia). The fish assemblages sampled at the two mid-water depths were significantly different demonstrating that this method could be used to investigate the vertical distribution and diel migration patterns of both pelagic and demersal fishes.Precision estimates under different sampling regimes showed that a soak time of 120 min and a sample size of at least 8 replicates per treatment would be optimal for sampling using pelagic stereo-BRUVs in tropical or warm-temperate areas. In order to account for the spatial and temporal variability of the system and to facilitate future comparisons across studies using this method, we encourage maximizing replication given the resources available while standardizing the soak time. Pelagic stereo-BRUVs may provide a useful, non-destructive method to improve our understanding on the ecology and behavior of fishes in pelagic ecosystems.